The role of human milk feeds on inotrope use in newborn infants with sepsis - Moliner-Calderón, Elisenda; Verd, Sergio; Leiva, Alfonso; Ginovart, Gemma; Moll-McCarthy, Pia; Figueras-Aloy, Josep (Frontiers in Pediatrics, 2023)
Background: Regarding neonatal hypotension, there is no certainty as to whether inotrope properties are beneficial or whether they may be harmful. However, given that the antioxidant content of human milk plays a compensatory role in neonatal sepsis and that human milk feeding has direct effects in modulating the cardiovascular function of sick neonates, this research hypothesized that human milk feeds might predict lower requirements of vasopressors in the management of neonatal septic shock. Method: Between January 2002 and December 2017, all late preterm and full-term infants attending a neonatal intensive care unit, with clinical and laboratory findings of bacterial or viral sepsis, were identified in a retrospective study. During their first month of life, data on feeding type and early clinical characteristics were collected. A multivariable logistic regression model was constructed to determine the impact of human milk on the use of vasoactive drugs in septic newborns. Results: 322 newborn infants were eligible to participate in this analysis. Exclusively formula-fed infants were more likely to be delivered via C-section, to have a lower birth weight and a lower 1-minute Apgar score than their counterparts. Human milk-fed newborns had 77% (adjusted OR=0.231;95%CI 0.07 to 0.75) lower odds of receiving vasopressors than exclusively formula-fed newborns. Conclusion: We report that any human milk feeding is associated with a decrease in the need for vasoactive medications in sepsis-affected newborns. This observation encourages us to undertake further research to determine whether human milk feeds mitigate the use of vasopressors in neonates with sepsis.